2013
DOI: 10.1063/1.4858656
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment effects on inflammatory marker profiles in saliva before and after 2 archwire changes

Abstract: Abstract. Periodontal tissue changes exerted by external forces in orthodontic treatment allow tooth movement. The changes in periodontal tissues i.e. inflammation can be monitored using gingival crevicular fluid (GCF). GCF is a component of saliva. Saliva could be used to monitor periodontal disease progression. The use of saliva to monitor periodontal tissues changes during orthodontic treatment is still unknown. Therefore, we observed the profiles of inflammatory markers namely creatine kinase ('CK), nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Acute inflammation of the periodontal tissues is among the changes that occur during orthodontic tooth movement. 6 Saliva is a main vehicle of defense in the oral cavity as it has a fundamental role in protecting & sustaining the health of the oral tissues. 10 Free radicals are produced from all the body tissues, including the oral cavity, during the physiological processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute inflammation of the periodontal tissues is among the changes that occur during orthodontic tooth movement. 6 Saliva is a main vehicle of defense in the oral cavity as it has a fundamental role in protecting & sustaining the health of the oral tissues. 10 Free radicals are produced from all the body tissues, including the oral cavity, during the physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the influence of NO on osteoclastogenesis. 6 There is controversy between different studies regarding the level of salivary NO during orthodontic treatment. Alarcon et al 13 found that the level of salivary NO increased from the seventh to the thirtieth day after the initiation of fixed orthodontic treatment in adult females and they suggested that future investigations are required to decide if the salivary nitric oxide level could be utilized as a marker for orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that hyalinization can occur in the most compressed areas of the periodontal ligament after application of orthodontic force on teeth. This hyaline zone has also been described as an area of focal aseptic necrosis (7) .…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxic conditions, cells will rely on anaerobic glycolysis. Many enzymes involved in an anaerobic metabolism can be potential markers (6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%